Exploring the Impact of Psychological Well-being on Organizational Commitment and Job Satisfaction in the IT Workplace - V., Hemanthakumara (Ushus Journal of Business Management, 2024)
The present study investigates the complex interconnections between psychological well- being, organisational commitment, and job satisfaction within the specific domain of Information Technology (IT) personnel. The Information Technology sector is renowned for its dynamic and high-pressure work settings, underscoring the significance of comprehending the interconnectedness between the well-being of its personnel, their organisational commitment, and job happiness. The research study utilised a quantitative research methodology, wherein data was gathered from a heterogeneous sample of 475 information technology workers engaged in different organisations across multiple geographical locations. The study employed a set of proven tools to assess psychological well-being (developed by Indira J Prakash, Sudha Bhogle), organisational commitment, and job satisfaction with good psychometric properties. The results of our study demonstrate a significant and positive correlation between psychological well-being and job satisfaction. There is a positive correlation between employees who report better levels of psychological well-being and their overall job satisfaction. This implies that businesses within the IT sector ought to prioritise the implementation of techniques that cultivate the mental and emotional well-being of their employees in order to augment both job satisfaction and productivity. Moreover, the findings of the study indicate that organisational commitment serves as a mediator in the association between psychological well-being and job satisfaction. Employees in the field of information technology who exhibit a greater level of dedication and loyalty towards their organisation are more inclined to express higher levels of job satisfaction. Therefore, fostering a sense of loyalty and connection among employees might potentially yield favourable outcomes in terms of their overall job happiness, which can be influenced by their psychological well-being.